Implementasi AI sebagai Kesiapan Mahasiswa Akuntansi untuk Menghadapi Dunia Kerja - Faradila Rahma; Pancawati Hardiningsih (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This is research examines how the study program curriculum influences the competency of accounting students. This research also examines the influences of the study program curriculunm and accounting student competencies on accounting students’ confidence in working with Artificial Intelligence (AI) so that their role is not completely replaced by AI. This research uses descriptive research with a quantitative approach carried out by distributing questionnaires to Bachelor of Accounting students at Stikubank University Semarang. Sampling used a purposive random sampling technique by collecting a sample of 116 respondents. This results show that the curriculum influences student competence. Apart from that, the research results show that the curriculum and competencies influence student’s self-confidence. Universities need a curriculum that provides various practice-related cases to improve competency related to the ability and operation of accounting software so that students have high self-confidence.